West Bengal Second Five Year Plan (1956-61) - Planning Commission (Planning Commission, 1956)
Planning signifies both a blue-print, and its translation into reality. Planning for a country inevitably becomes a long-term affair. It should naturally extend over several decades. For convenience of execution, however, it is desirable to break it up into Plans of a definite duration. At the first instance it focusses our attention on the immediate objective and thus helps a realistic approach. A set target for a set period accentuates our endeavour. Our Plans have been accordingly divided into periods of five years. the First Plan has been completed; we have started the Second Plan.
Government of West Bengal